1870 Va. Acts 1206, tit. 54, ch. 191, § 7 (1873)] - (:unkn) unknown (My University, 1870)
If a person habitually carry about his person, hid from common observation, any pistol, dirk, bowie knife, or any weapon of the like kind, he shall be fined fifty dollars, and imprisoned for not more than twelve months in the county or corporation jail. The informer shall have half of such fine.
Keywords: CARRY - CONCEALED